Dynamics of functional state of sensory visual system of technical specialties students during educational day - Rovniy A.S; Buren' N.V (Kharkov National Pedagogical University, 2010)
The problem of adaptation of students of freshmen is examined to the educational loadings during educational day. In research took part 93 students in the age of 17-18. It is set that the visual sensory system is the indicator of reacting of organism on the different types of fatigue - psychical, mental, physical. It is rotined that playing table tennis is a substantial mean in renewal of functions of the visual sensory system. It is marked that the natural increase of adaptation to the educational loadings reduces the level of functional changes of the visual sensory system.